Exploring the interplay between microplastics and biofilms in freshwater - Jordão, Luisa (2023)
Plastic inevitably accumulates in the environment becoming a persistent. In the present work, we aim at documenting MPs occurrence in three collection spots of the biggest European artificial lake over one year period using infrared microscopy. Scanning electron microscopy was used to evaluate MPs colonization by biofilms. PE was the most abundant polymer and biofilms were identified in all plastics.